Effect of Viscosity Parameter on Numerical Simulation of Fire Damaged Concrete Columns - Iqrar Hussain; Muhammad Yaqub; Adeel Ehsan; Safi Ur Rehman (Salehan Institute of Higher Education, 2019)
The assessment of the residual strength of post-heated concrete structural members in a professional way is a prime factor to take a decision about the restoration or destruction of fire-damaged structure. This Paper explores the numerical modelling of RC square columns damaged by exposure to heat at 5000C, unjacketed. Software ABAQUS was used for numerical modelling of fire damaged compression member i-e column. The main objective of this study is prediction of axial load and axial deformation of fire damaged concrete using finite element studies. Moreover, a parametric nonlinear finite element (FE) research is carried out to check the effect of viscosity parameters on numerical simulation of fire damaged concrete columns. For the said objectives, numerical simulation of existing experimental study of fire damaged RC columns is conducted with varied values of viscosity parameters. The numerical analysis (Finite Element Modeling) indicated that axial load capacity decreases and axial deformation increases after exposure to fire. The experimental and numerical studies are compared in terms of load displacement analysis. The use of optimum viscosity parameter and its definition to FEM improves significantly the performance of convergence and reduces analysis time of numerical simulations of RC square columns. Moreover, a good agreement was found between the experimental and the finite model results.